Amateur Male Runners and the Construction of Athletic Identity in the Marathon Field - Bareckas, Karolis (Sociologija. Mintis ir veiksmas, 2024)
Drawing on Bourdieu’s concepts of field, capital, and habitus, this article examines the construction of athletic identity among amateur male runners. Based on eight semi-structured interviews, it highlights the motivations that lead men into the field of running, shifts in body perception, and the role of gender in identity formation. Running emerges as a crucial means of self-discovery, discipline, and social recognition. Marathon runners often follow a shared trajectory of professionalization: initial goals linked to health and well-being gradually give way to the pursuit of competition, rivalry, and testing of personal limits. Preparing for a marathon involves navigating between positive and negative bodily experiences; when injury occurs, athletic identity may fracture, provoking intense emotional struggles. The article argues that bodily transformation becomes inseparable from identity, enabling men to construct versions of themselves that resonate with contemporary norms of masculinity. The athletic body operates as symbolic capital, reinforcing masculine identity and securing one’s position within the field of running.